Odpowiedź :
Odpowiedź:
1 zadanie:
2z - y = 6 - 4 = 2
5x + 2y + z = -5 + 8 + 3 = 8
2xz + y = 4 + 4 = 8
x + z = -1 + 3 = 2
2y + 6x - 8 + (-6) = 2
yz + 10x = 7 + (-10) = -3
(z - x) : 2 = 4 : 2 = 2
3z - 2y + x = 9 - 8 + (-1) = 0
xyz + 10 = 6 + 10 = 16
y - z + x = 4 - 3 + (-1) = 0
12 - 5z - x = 12 - 15 - (-1) = -2
Zadanie 2:
a) (-32) - 20 = -62
b) 50 - 27 = 23
c) 20 + 4 = 24
d) -25 - 20 = -45
e) 8 + 3 = 11
f) 2 - 2 = 0
Szczegółowe wyjaśnienie:
Zadanie 1
x+z = -1+3 = 2
3z-2y+x = 3*3-2*4+(-1) = 9-8-1 = 0
2z-y = 2*3-4 = 6-4=2
2y+6x = 2*4+6*(-1) = 8-6=2
xyz+10 = (-1)*4*3+10 = -12+10= -2
5x+2y+z = 5*(-1)+2*4+3 = -5+8+3= 6
yz+10x = 4*3+10*(-1) = 12-10 = 2
y-z+x = 4-3+(-1) = 1-1 = 0
2xz+y = 2*(-1)*3+4 = -6+4 = -2
(z-x):2 = [3-(-1)]:2 = (3+1):2 = 4:2= 2
12-5z-x = 12-5*3-(-1) = 12-15+1 = -3+1 = -2
Zadanie 2
7a-20 = 7*(-6)-20 = -42-20 = -62
50-3x = 50-3*9 = 50-27 = 23
10m - m² = 10*2-(2)² = 20-4=16
w²-4w = (-5)²-4*(-5) = 25+20 = 45
2z³+3z = 2*1³+3*1 = 2*1+3=2+3=5
4t-2 = 4*(0,5)-2 = 2-2=0
Pozdrawiam :)